A new method for the estimation of the number of motor units in a muscle: 1. Control subjects and patients with myasthenia gravis. Issue 8 (August 1974) - Ballantyne, John P.; Hansen, Stig
Abstract : A new method, incorporating on-line computer analysis, is described for the estimation of the numbers of motor units in human muscle. The results obtained in the extensor digitorum brevis muscle in normal subjects and patients with myasthenia gravis are presented. These indicate that the numbers of motor units in that muscle in patients with myasthenia gravis are within the normal range, in contrast with the reduction in numbers reported by other workers using a different technique. Evidence is presented to suggest that the discrepancy in these results is due to increased sensitivity and discrimination of the computerized method. Several hypotheses on the aetiology of a number of neuromuscular diseases, based on the results of the other method, may require reevaluation.